A New Model to Determine Passive Intermodulation Terms When Non-Contributing Carriers are Added to Classical Scenarios - Davide Smacchia (IEEE, 2021)
This paper provides a new theoretical model for the characterization of passive intermodulation behaviour when non-contributing carriers (i.e., carriers which do not directly affect the particular non-linear contribution under analysis) are added to classical two or three carriers scenarios. According to traditional models, the power of a particular passive intermodulation frequency term is only related to the contributing carriers which combines in non-linear way to generate this term, thus the presence of additional (i.e., non-contributing) carriers should not affect to the predicted power of such an intermodulation product. However, recent laboratory tests reveal that non-contributing carriers do reduce the power of unrelated passive intermodulation terms. A heuristic model is proposed in this work to explain this effect, which shows a good matching with measured results already published in the technical literature. The study is focused in third order non-linear contributions, as being the most critical in practical applications.